Quality of life of the HIV patients in Agra: a cross sectional study - Meena, Sunil K.; Misra, Sunil K.; Chaudhary, Shailendra S. (International Journal Of Community Medicine And Public Health, 2018)
Background: With antiretroviral therapy (ART) for human immunodeficiency virus infection (HIV) coming into picture, quality of life (QOL) has gained importance. Knowledge on the factors affecting QOL would be helpful in making important policy decisions and health care interventions. The aim of this study is to assess the quality of life of people living with HIV and to identify the factors influencing their QOL. Methods: The Cross-sectional study was done among 160 HIV patients registered with ART Centre, at SNMC Agra (UP), India. QOL was assessed using HIV specific WHOQOLHIV-BREF questionnaire which has six domains. Association were find out by using chi square test for categorical variables and ANOVA were used for comparisons means scores among continuous variables. Correlation between continuous quantitative variables was found out by Pearson correlation coefficient. Results: Mean age of the study subjects was 37.89 years and 61.2% of the participants were males. Quality of life score was highest in level of independence domain (12.79±2.28) and lowest in SRPB domain (10.51±3.63). A significant negative correlation (-0.49) was observed between age and physical domain. Male Subjects had significant better mean score in social and environmental domain. Family support associated with social relationship and psychological domain. Higher CD4 count is associated with better in psychological and SRPB domain. Younger age, female gender, rural background, shorter duration of HIV, non-intake of ART were the high risk factors of poor QOL. Conclusions: Interventions such as ART, family, vocational and peer counselling would address these modifiable factors influencing QOL, thereby improving the QOL of PLWH.